2012
DOI: 10.1016/j.crohns.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional analysis of intestinal organic cation/l-carnitine transporter (OCTN) in Crohn's Disease

Abstract: The present data reveal that OCTN protein levels appear to be similar in intestinal tissue from Crohn's Disease patients and controls. Overall, ileal carnitine transport appears to as well equal in Crohn's Disease and control groups. However, there was a trend towards higher carnitine transport in subjects with OCTN1 and OCTN2 mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Carnitine supplementation in these situations raises the tissue carnitine concentrations to only 5–10% of normal, and this seems sufficient for normal function 46 . Even though decrease-of-function mutations in the OCTN transporters have been demonstrated in a significant number of patients with IBD and CD, many of these patients do not show any evidence of plasma carnitine deficiency 47 . This may be accounted for by differences between plasma and tissue carnitine levels since human studies have not reported intestinal tissue carnitine levels.…”
Section: Discussionmentioning
confidence: 91%
“…Carnitine supplementation in these situations raises the tissue carnitine concentrations to only 5–10% of normal, and this seems sufficient for normal function 46 . Even though decrease-of-function mutations in the OCTN transporters have been demonstrated in a significant number of patients with IBD and CD, many of these patients do not show any evidence of plasma carnitine deficiency 47 . This may be accounted for by differences between plasma and tissue carnitine levels since human studies have not reported intestinal tissue carnitine levels.…”
Section: Discussionmentioning
confidence: 91%
“…They are located within the IBD5 gene, which codes two transporters for carnitine 2: OCTN1 and OCTN2. The first one decreases transport of carnitine and increases transport of cations, while the second one inhibits carnitine uptake [13]. DLG5 (discs large homolog 5) gene, which belongs to MAGUK (membrane-associated guanylate kinase), is another SNP associated with mucosal membrane integrity.…”
Section: Crohn's Disease and Ulcerative Colitisgenetic And Molecular mentioning
confidence: 99%
“…In 2007, Hampe et al [15] proved that polymorphism in Thr300Ala in the AT-G16L1 gene (bacterial autophagy) is associated with CD. A meta-analysis has been conducted revealing that variant rs2241880/T300A of this gene may contribute to CD development in childhood; however, it has not been confirmed for UC [13]. Therefore, it seems that AT-G16L1 is an SNP gene for CD exclusively.…”
Section: Crohn's Disease and Ulcerative Colitisgenetic And Molecular mentioning
confidence: 99%
See 1 more Smart Citation
“…The solute carrier family 22 member 4 ( SLC22A4 ) gene is important for barrier function, encoding an organic cation transporter protein involved in the movement of proteins across the membrane of epithelial cells. McCann et al considered the risk variant (rs1050152 at position 503F) which has a higher transport activity compared with the wild-type gene, leading to inappropriate transport of organic cations across the intestinal epithelial barrier [71]. As their example of a mutant that affected immune response, they utilised a variant in the gene encoding interleukin-10 ( IL10 ).…”
Section: In Vitro Approaches To Identifying Bioactive Food Componementioning
confidence: 99%